Dose-Response Effect of Dietary Nitrate on Muscle Contractility and Blood Pressure in Older Subjects: A Pilot Study - Gallardo, Edgar J; Gray, Derrick A; Hoffman, Richard L; Yates, Brandon A; Moorthi, Ranjani N; Coggan, Andrew R (The journals of gerontology. Series A, Biological sciences and medical sciences, 2021)
We have recently demonstrated that dietary nitrate, a source of nitric oxide (NO) via the nitrate → nitrite → NO enterosalivary pathway, can improve muscle contractility in healthy older men and women. Nitrate ingestion has also been shown to reduce blood pressure in some, but not all, studies of older individuals. However, the optimal dose for eliciting these beneficial effects is unknown. A pilot randomized, double-blind, placebo-controlled crossover study was therefore performed to determine the effects of ingesting 3.3 mL/kg of concentrated beetroot juice containing 0, 200, or 400 µmol/kg of nitrate in 9 healthy older subjects (mean age 70 ± 1 years). Maximal knee extensor power (Pmax) and speed (Vmax) were measured ~2.5 hours after nitrate ingestion using isokinetic dynamometry. Blood pressure was monitored periodically throughout each study. Pmax (in W/kg) was higher (p < .05) after the lower dose (3.9 ± 0.4) compared to the placebo (3.7 ± 0.4) or higher dose (3.7 ± 0.4). Vmax (in rad/s) also tended to be higher (p = .08) after the lower dose (11.9 ± 0.7) compared to the placebo (10.8 ± 0.8) or higher dose (11.2 ± 0.8). Eight out of 9 subjects achieved a higher Pmax and Vmax after the lower versus the higher dose. These dose-related changes in muscle contractility generally paralleled changes in breath NO levels. No significant changes were found in systolic, diastolic, or mean arterial blood pressure. A lower dose of nitrate increases muscle speed and power in healthy older individuals, but these improvements are lost at a higher dose. Blood pressure, on the other hand, is not reduced even with a higher dose.